The Relationship between Organizational Culture and Employee Work Motivation at the Building Management Unit of the Indonesian Corruption Eradication Commission (KPK) - Meta Meidina Risanti; Edison C. Sembiring (Eastasouth Institute, 2026)
Organizational culture plays a fundamental role in public sector institutions, as it shapes employees’ attitudes, behaviors, and work patterns. A strong and well-internalized organizational culture is widely recognized as a key factor in fostering employee work motivation in carrying out organizational duties and responsibilities. This study aims to examine the relationship between organizational culture and employee work motivation at the Building Management Unit of the Indonesian Corruption Eradication Commission (KPK). This research adopts a quantitative approach using a survey method. Data were collected through structured questionnaires developed based on organizational culture dimensions and work motivation indicators as formulated in the research framework. The study population consisted of all employees within the unit under investigation, with the sampling technique applied in accordance with established methodological standards. Statistical analysis was employed to examine the relationship between organizational culture and employee work motivation, both partially and simultaneously. The findings indicate that organizational culture has a significant relationship with employee work motivation. Each organizational culture dimension examined contributes meaningfully to shaping employees’ levels of work motivation. These results highlight the strategic importance of strengthening organizational culture as a means of enhancing employee motivation, particularly within public sector institutions that demand high standards of professionalism and integrity.